ANTHROPOLOGICAL SEARCH FOR VALUE ORIENTATIONS OF A NEW CULTURE BY AURELIUS AUGUSTINE - V. V. Kuzmenko; V. O. Boniak; I. A. Serdіuk (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The article is aimed to reveal the essence of the eternal problem, comprehended by Augustine Aurelius in the culture of the early Middle Ages – the focus of the value orientations of the anthropological search. Theoretical basis. Only in the twentieth century, various aspects of Augustine’s creative legacy became the subject of scientific research by many authors. As the direction of their scientific research, the problem of the relationship of reason, faith, knowledge, which has risen sharply in medieval Christian culture, has been considered. The logical outcome of these studies was the assertion that for Augustine Platonism was the main of the philosophical teachings of antiquity; that Augustine, being in line with Christian philosophy, considered the understanding of the aesthetic perfection of the Divine creation of the world as the sense of human life. The analysis of their works gives reason to argue that the definition of the human essence – the Augustine’s anthropological problems, was practically not addressed by representatives of domestic and foreign philosophical thought, and therefore remained undiscovered. Originality. The authors have proved that the definition of the human essence by Augustine is in the correlation with his answers to questions about the nature of the origin of man, about the secrets of being, etc. The ethical ideal of the thinker has been revealed, which is systematically formed in his works. Conclusions. The thesis has been substantiated that the anthropological views of Augustine Aurelius are in correlation with his epistemological judgments. Only by knowing the order of things in the universe, determined by the will of the Lord, we will know also the order of our value orientations. The basis of the philosophical comprehension of the human essence by Augustine Aurelius is a series of questions that constantly arise before mankind – about the nature of its appearance, about the secrets of human existence, the sense of life, death and immortality, etc. The ethical ideal of the thinker is an eternal city that is not based on human nature, it is too volatile, therefore it is only to a small extent subject to research, but on a Divine basis – the Christian idea.